2023
DOI: 10.3390/coatings13020444
|View full text |Cite
|
Sign up to set email alerts
|

An Enhancement of Compositional Stability of Phase Change Materials by Lamination with Aluminum Sheet

Abstract: The wax leakage from shape-stabilized phase change materials (SSPCMs) is a limitation because it reduces their functionality. In this work, an enhancement of the compositional stability of SSPCMs formed by high-density polyethylene (HDPE) and paraffin wax blends through a lamination by aluminum (Al) foil was studied. The materials' thermal conductivity was enhanced by adding expanded graphite (EG). The lamination of SSPCMs is the simplest method of reducing leakage, but it suffers from poor adhesion between po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Techniques such as lamination with aluminum foil and the inclusion of adhesion promoters, such as maleated polyethylene, can enhance compositional stability and mitigate leakage. 23,24 Collectively, these strategies aim to improve the thermal performance and stability of polymer-based SSPCMs. Some of the challenges faced by polymer-based SSPCMs with their underlying causes and the current strategies employed to mitigate them have been discussed in Table 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques such as lamination with aluminum foil and the inclusion of adhesion promoters, such as maleated polyethylene, can enhance compositional stability and mitigate leakage. 23,24 Collectively, these strategies aim to improve the thermal performance and stability of polymer-based SSPCMs. Some of the challenges faced by polymer-based SSPCMs with their underlying causes and the current strategies employed to mitigate them have been discussed in Table 3.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer‐based SSPCMs may be vulnerable to humidity, which may cause the PCM and polymer matrix to degrade. Techniques such as lamination with aluminum foil and the inclusion of adhesion promoters, such as maleated polyethylene, can enhance compositional stability and mitigate leakage 23,24 . Collectively, these strategies aim to improve the thermal performance and stability of polymer‐based SSPCMs.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, this is carried out by blending PCMs with other polymers or coating the PCMs. For instance, paraffin wax PCM was blended with highdensity polyethylene (HDPE) and laminated with aluminum foil to eliminate leakage problems [22]. However, in a previous example of research, a large reduction in latent heat was observed during the formation of form-stable PCMs.…”
Section: Introductionmentioning
confidence: 99%